EFEKTIVITAS INTERVENSI COUNTING BLESSING UNTUK MENINGKATKAN KEBAHAGIAAN DI TEMPAT KERJA - Dian Nafis, Fawwazaidan; Rejeki, Asri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Happiness in the workplace is an important factor in improving employees' well-being and productivity. However, at PT X, some employees still feel unhappy, which may affect their performance. This study aims to evaluate the effectiveness of the positive psychology intervention Counting Blessing in increasing employee happiness. Using a pre-experimental design with a quantitative approach, the study involved three employees of PT X who participated in the intervention program for two weeks. Data were collected through questionnaires measuring aspects of job satisfaction, engagement, and affective organizational commitment using the SHAW Scale instrument. Data analysis was conducted using paired sample t-test and N-Gain score. The results showed a Sig. (2-tailed) value of 0.01, indicating a significant difference in employee happiness after the intervention (p < 0.05). Additionally, the N-Gain test showed an increase in happiness with an average score of 0.679 (67.859%) in the